Dynamics and genetic regulation of leaf nutrient concentration in barley based on hyperspectral imaging and machine learning - Grieco, Michele (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2021 The Authors. Published by Elsevier B.V. All rights reserved.